THE EFFECTIVENESS OF CONSTRUCTIVISM APPROACH TOWARDS ACITIVITY AND LEARNING RESULT ON MICROSCOPE MATERIAL - Rohaeni, Siti; Sukaesih, Sri; Martin H.B., Putut (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Abstract ___________________________________________________________________ This study aimed to describe the effectiveness of a constructivism approach to the activity and student learning result in materials microscopy in SMP Negeri 2 Welahan, Jepara. This study is a pre-experimental research design one shoot case study. The study population was all students of class VII consists of six classes (VIIA-VIIF). Samples were taken using purposive sampling, consists of two classes, namely VIIE class consisting of 38 students and VIIF class consisting of 37 students. The independent variables in this study are materializing learning with a constructivism approach, and the dependent variable is the activity and student learning result. Data captured using student activity observation sheet, sheet materialize questionnaire study with a constructivism approach, interview teachers, and the post-test. Based on the results of the data, analysis, and discussion, student activities classically reached 89.5% (VIIE) and 86.5% (VIIF). Classical completeness of student learning result was 92.1% (VIIE) and 89.1% (VIIF). Materialize learning with a constructivist approach shows very good and good result, both in class VIIE and VIIF. Teachers give a positive response to a constructivism approach to learning. It can be concluded that effective learning with a constructivism approach to the activity and student learning result in materials microscopy.